Effect of macnetic water and urea spray on yield of two lettuce cultivars (regina dei ghiacci and great lakes 118) in nft culture system. - AL-Dabbagh, Abdullah M. S.; Dawod, Zuhair A. (Journal of Kerbala for Agricultural Sciences, 2018)
This research was conducted in unheated plastic house at Horticulture and Landscape Design Department, College of Agriculture & Forestry, Mosul University, during the growing season 2012-2013. The aim of this study was to investigate the effect of magnetic water and urea spray on the yield of two lettuce cultivars in NFT culture system, transplants of two lettuce varieties (Regina dei ghiacci and Great Lakes 118) were continuously treated by three intensities of magnetic water (0 ,750 and 1500 gauss) during the experiment period and two foliar sprays of pure urea at three concentrators (0, 0.125 and 0.250 %) were applid. Asplit-split plot system within a randomize complete block design (RCBD) with three replicates was used to carry out this experiment. Results data could be summarized as follows the Regina dei ghiacci variety has been significantly superior in the percentage protein . with Great Lakes 118 variety. while the Great Lakes 118 variety was significantly superior in percentage of the percentage leaf chlorophyll content. All urea treatments caused a significant increase all lettuce parameters as compared with control treatment. Using magnetic water at 750 gauss intensities caused a significant increasment in most yield parameters as compared with control treatment. Mean while Generally, the interaction treatments caused extra effect on vegetative characteristics as compared with the effect of each single factor.